Symptoms of post-traumatic stress among victims of school bullying - Luky Kurniawan; Natri Sutanti; Zalik Nuryana (International Journal of Public Health Science (IJPHS), 2022)
School bullying is a critical issue among students that can promote some mental health issues. Some studies had found that severe or frequent bullying can lead to the development of post-traumatic stress symptoms such as avoidance behaviours and anxious feelings. However, school bullying is difficult to observe due to the complexity factors such as cultural background, peer pressure and academic problems. The study aimed to investigate the symptoms of post-traumatic stress among victims of school bullying. The study employed a descriptive qualitative research design. The data was collected by using a questionnaire to 42 students from two vocational high schools in Yogyakarta who had severe or frequent experience of school bullying. The results revealed that 40 per cent of participants showed one or more symptoms of post-traumatic stress such as feeling persistently avoiding to the perpetrators and feeling extremely anxious about the potential being bullied again. Meanwhile, 60 per cent participants experienced some other difficult emotions such as anger, revenge, disappointment, and sadness. The results also showed that the two biggest changes experienced by students after bullying were becoming more silent and being frequently anxious compared to before being bullied. The study suggests the need for further research to investigate the level of post-traumatic stress experienced by the students and the urge for anti-bullying curriculum in both schools to prevent the serious consequences of bullying.